“He Used to Be A Late Talker”: Parents’ Narration Of A Five-Year-Old Child Named Hasan - Emy Sudarwati; Ary Setya Budhi Ningrum (JEELS (Journal of English Education and Linguistics Studies), 2021)
This narrative inquiry is based on the lived experiences of parents who have a speech delayed child. A child with a language delay must go through in order to appropriately have strong competence in the language learning process. The data were derived from parents’ stories, a speech therapy progress book, medical records, and video recordings of classroom activities. Findings were focused on the thorough process a research subject has undergone to finally survive in catching up his lag of language development compared to the mainstream children of his age. After four years of intensive labor requiring parental involvement and three years of programmed therapy, the research subject achieves improvement milestones that enable him to catch up to conventional children's language development, which he should have completed. More research into the deployment of other linguistic aspects is needed to provide a clear picture of the development of his language learning.